#### Answer

(x-3)(x-6)

#### Work Step by Step

$x^{2}$ - 9x + 18 = (x- 3)(x__)
step 1. Enter x as the first term of each factor
$x^{2}$ - 9x + 18 = (x- 3)(x__)
Step 2. To find the second term of each factor, we must find two integers whose product is 18 and whose sum is -9
List pairs of factors of the constant, 18
(1,18)(2,9)(-2,-9),(3,6)(-3,-6)
step 3. The correct factorization of $x^{2}$ - 9x + 18 is the one in which the sum of the Outside and Inside products is equal to -9x.
So (-3,-6) satisfy the condition
$x^{2}$ - 9x + 18= $x^{2}$ - 3x - 6x+ 18 = (x-3)(x-6)